Therapeutic effect of dihydroartemisinin on Alzheimer’s disease model mice with senile macular degeneration - Gao Han; Gong Xuewu; Zhang Meng; Wang Yuejing; Wang Yuchun; Zhang Keshuang; Yao Hongbo (European Journal of Medical Research)
Abstract Objectives This study focuses on the preventive and therapeutic effects of Dihydroartemisinin (DHA) on Alzheimer’s disease (AD) model mice and the effects of DHA and donepezil on amyloid β-protein deposition and autophagy in nerve cells. Methods Six autophagy related targets were selected for molecular docking with DHA to predict the affinity between DHA and the target. The AD mouse model was established and treated with donepezil and DHA, respectively. Morris water maze was used to detect the spatial learning and memory ability of AD mice. Hematoxylin eosin (he) staining was used to observe the structural changes of cerebral cortical neurons and retina, and transmission electron microscope was used to observe the structural changes of mitochondria and synapses. Immunohistochemistry (IHC) and immunofluorescence staining were used to detect the deposition of amyloid beta protein. Western blot was used to detect the expression of apoptosis and autophagy related proteins in the brain tissue of mice in each group. Results The results of molecular docking showed that the selected active compounds had good binding activity with the target. The binding energy between DHA and Aβ, Bcl-2, ATG5, LC3, Caspase3, LAMP1 is −5.7, −7.0, −5.8, −7.2, −6.9 kcal/mol. The water maze test showed that compared with the wild type (WT) group, the spatial memory ability of AD model group mice (5× FAD) was significantly decreased, and the search time (27.62 ± 6.51 s vs. 282.80 ± 17.15 s) and average path (106.30 ± 29.65 cm vs. 993.20 ± 135.80 cm) were significantly prolonged. The application of donepezil and DHA significantly shortened the exploration time and average path (donepezil: 116.10 ± 10.58 s, 529.40 ± 106.00 cm; DHA: 99.71 ± 14.22 s, 373.30 ± 60.97 cm). The path to find the platform in DHA treatment group was shorter than donepezil treatment group (P < 0.05). HE staining showed that the arrangement of nerve cells in 5× FAD mice was disordered, and IHC showed that amyloid β-protein deposition was obvious. DHA and donepezil could improve the damage of cerebral cortex structure and reduce the deposition of extracellular amyloid β-protein in AD mice. Transmission electron microscopy showed that DHA and donepezil could reduce mitochondrial vacuolation and synaptic edema. The above results showed that DHA treatment effect was better than donepezil. Compared with the conventional feeding group, autophagy and apoptosis related proteins B-cell lymphoma-2 (BCL2) and anti-thymocyte globulin (ATG) were significantly down regulated in the 5× FAD group, and the expressions of BCL2 and ATG were increased after treatment with DHA and donepezil. Conclusions DHA combined with BCL2 and ATG protein, through promoting autophagy protein, can reduce the damage of cerebral cortex structure in AD mice, reduce the deposition of extracellular β-amyloid protein, and then improve the memory ability of AD model mice. DHA treatment is superior to donepezil monotherapy.